Influência da estimulação tátil nociva e do uso da sacarose intra-oral no desenvolvimento sensório-motor em modelo experimental de dor neonatal - Santos, Isabela Azevedo Freire (2018)
Background: Preterm newborns are daily exposed to painful procedures at Intensive Care Units. Despite this, repercussions of neonatal pain in long term and the use of oral sucrose to relieve pain related to these procedures are not well evidenced. Objectives: 1) To synthesize existing data in the literature (systematic review) regarding the effects of neonatal pain on motor development in long term; 2) To evaluate the effects of sucrose on sensory and motor functions in an experimental model of neonatal pain from birth to adulthood. Method: A systematic search of studies was performed in four databases (PubMed, Scopus, Scielo e LILACS) by two investigators, with the key-words “Infant, newborn”, “Infant, premature”, “Pain” and “Motor skills”. For methodological assessment, Newcastle-Ottawa Assessment Scale (NOS) was used. 2) An experimental study was performed in rat pups (n=38; 18 male and 20 female) submitted to the experimental model of neonatal pain. Animals were allocated in four groups: 1) Tactile noxious stimulation + sucrose intervention (n=9; 5 male and 4 female); 2) Tactile noxious stimulation + morphine intervention (n=9; 5 male and 4 female); 3) Tactile noxious stimulation + drinking water intervention (n=9; 3 male and 6 female); 4) Control (tactile and non-noxious stimulation) (n=11; 5 male and 6 female). Thermal latency (hot plate), paw withdrawal threshold (von Frey filaments), muscle strength (grip strength) and locomotion speed (activity monitor) were evaluated at 15, 30, 60 and 90 post-natal days. On days 32, 62 and 92, experimental model of neonatal pain was reinduced in these animals and paw withdrawal threshold and thermal latency were reassessed. Results: 1) Eleven studies were found, however after risk of bias assessment, only two studies were selected. Low scores on NOS scale (NOS ≤ 5) were observed on the analyzed cohorts. A relation between the number of painful procedures performed in premature neonates and lower motor and cognitive development index of these subjects with 18 months was observed. Additionally, pain reactivity was reported as a predictive factor for the quality of motor activities at the age of 8 months. 2) There was higher thermal latency at 15 days in sucrose male animals and lower latency in females treated with sucrose at 60 days in relation to the control group. There was a higher paw withdrawal threshold in the animals of the morphine, water and sucrose groups in relation to the control. It was observed a decrease on thermal latency and paw withdrawal threshold, increase in grip strength, and decrease in speed over time in all groups. When comparing gender at 60th postnatal day, sucrose-treated animals presented higher thermal latency (males than females) and higher locomotion speed (females than males). In the morphine and control groups, there was a higher paw withdrawal threshold in females and males, respectively. There were no differences between sexes in other groups. Conclusion: Low methodological quality and the absence of published studies permit to affirm, on a limited extent, that neonatal pain influences motor development from the first days of life until the early childhood. It is suggested that sucrose and morphine have analgesic effects in short term and antihyperalgesic effect in long term. Further studies are recommended to better understand the effects of sucrose and its effects on different sexes throughout life.